we are given
![x^2y-2xy-24y=y(x^2-2x-24)](https://tex.z-dn.net/?f=x%5E2y-2xy-24y%3Dy%28x%5E2-2x-24%29)
now, we can factor out right side term
![x^2-2x-24=x^2-6x+4x-6*4](https://tex.z-dn.net/?f=x%5E2-2x-24%3Dx%5E2-6x%2B4x-6%2A4)
![x^2-2x-24=(x-6)(x+4)](https://tex.z-dn.net/?f=x%5E2-2x-24%3D%28x-6%29%28x%2B4%29)
now, we can plug back
and we get
so,
.............Answer
If the question is 5m^2 the answer is 80. And if the question is 5m2 then it is 40
Answer:
2(5g+3h+4)
10g+6h+8
Please that is the answer
-3y = x...so we sub in -3y for x in the other equation
-x + 7y = 70
-(-3y) + 7y = 70
3y + 7y = 70
10y = 70
y = 70/10
y = 7
so we sub in 7 for y in either of the original equations to find x
-3y = x
-3(7) = x
-21 = x
so ur solution is (-21,7)